(untitled) (Perspectivas em Ciência da Informação, 2022)
The article presented here aims to assess how management instruments are referenced in Brazilian legislation, within the scope of the national and state Executive Power. The methodology used in this research was a qualitative one, which initially sought to define the concepts and uses presented in the national and international bibliography on records management instruments, namely, classification scheme and schedule of disposal of records Documental research was used in order to verify the existence of instrument concepts in the legislation; the determination of its elaboration and use; the establishment of production procedures and responsibility for their respective approvals. In terms of archival legislation in Brazil, our results allow us to state that there has been great progress in recent years, with regard to management instruments, however, in a general view, the scenario still seems far from ideal, since one still cannot count on a national archival policy, and not even a state one, since classification scheme and schedule of disposal of records are not always applied and used systematically in public administration.